SANTUNAN ANAK YATIM SEBAGAI WUJUD KEPEDULIAN MAHASISWA KKN UNIVERSITAS ISLAM AL-IHYA KUNINGAN KELOMPOK 10 DI DESA MUNCANGELA - Budi Hidayah; Iis Wahyuni; Jumsari; Noor Khaliza; Risa Suci Amalia; Cahya (Universitas Islam Al-Ihya Kuningan, 2024)
Community Service through the Unisa Kuningan Real Work Lectures activity for 40 days in Muncangela Village through a religious program , namely Donation for Orphans. As a form of concern and education for all Muslims to love orphaned children. Al Ihya Kuningan Islamic University KKN students group 10 have carried out donation activities for orphans in Muncangela village, Cipicung District, Kuningan Regency on September 9 2024. The implementation of the activity program is carried out in two stages, namely: (1) coordination; (2) distribution, through an orphan compensation program, although the amount of compensation is not large, it is meaningful for the orphans, of course with the hope of inviting benefactors, rich people and Muslims to take part in caring for orphans around them. This activity is also a work program for KKN students from groups of 10 Muncangela villages as a series of closing activities. Unisa KKN group 10 students became initiators and were able to make the public aware of the importance of caring for orphans, and as an application of the prophet's hadith narrated by Bukhari and Muslim.